2021
DOI: 10.3390/pharmaceutics13070988
|View full text |Cite|
|
Sign up to set email alerts
|

The Multifaceted Role of Extracellular Vesicles in Glioblastoma: microRNA Nanocarriers for Disease Progression and Gene Therapy

Abstract: Glioblastoma (GB) is the most aggressive form of brain cancer in adults, characterized by poor survival rates and lack of effective therapies. MicroRNAs (miRNAs) are small, non-coding RNAs that regulate gene expression post-transcriptionally through specific pairing with target messenger RNAs (mRNAs). Extracellular vesicles (EVs), a heterogeneous group of cell-derived vesicles, transport miRNAs, mRNAs and intracellular proteins, and have been shown to promote horizontal malignancy into adjacent tissue, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 213 publications
(430 reference statements)
1
19
0
Order By: Relevance
“…EVs have also been found to be major players of drug resistance in glioblastomas by transporting anti-cancer agents out of the tumor microenvironment [ 21 ], highlighting the importance of targeting EVs in the endeavor of developing novel therapeutic strategies for this disease. miRNAs using EVs as their nano-vehicles in glioblastomas have been thoroughly reviewed elsewhere [ 22 ].…”
Section: Drivers Of Emt In Glioblastomamentioning
confidence: 99%
“…EVs have also been found to be major players of drug resistance in glioblastomas by transporting anti-cancer agents out of the tumor microenvironment [ 21 ], highlighting the importance of targeting EVs in the endeavor of developing novel therapeutic strategies for this disease. miRNAs using EVs as their nano-vehicles in glioblastomas have been thoroughly reviewed elsewhere [ 22 ].…”
Section: Drivers Of Emt In Glioblastomamentioning
confidence: 99%
“…Many studies have shown that when endothelial cells are activated, they secrete a number of nanovesicles that would help initiate and aggravate the atherogenic process. The term nanovesicles, also known as extracellular vesicles (EVs), bring together two separate classes of small particles of the order of nm called exosomes (40–100 nm) and microparticles (MPs) or microvesicles (MVs) (100–1,500 nm) that are released by cells physiologically, and in pathological conditions this release is amplified ( Alexandru et al, 2021 ; Simionescu, Zonda, Petrovici, & Georgescu, 2021 ). These vesicles are rich in lipids, proteins, and microRNAs (miRNAs) and have the ability to regulate posttranscriptional gene expression in target cells ( Constantin, Filippi, Alexandru, Nemecz, & Georgescu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…EVs exhibited diagnostic potential in different pathologies [ 24 , 25 ], as well as biomarker potential in the context of treatment response and disease recurrence [ 26 , 27 , 28 , 29 , 30 , 31 ]. Additionally, EVs contain distinctive miRNA signatures [ 14 ], which change under pathological conditions [ 24 , 32 , 33 ] and could be applied in clinical settings as biomarkers for prognosis and therapeutic response monitoring. A particular type of EV is represented by microvesicles (MVs), which are phosphatidylserine (PS)-positive EVs (100–1000 nm) with variable shapes generated by blebbing of the plasma membrane of activated cells [ 11 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, EVs contain distinctive miRNA signatures [ 14 ], which change under pathological conditions [ 24 , 32 , 33 ] and could be applied in clinical settings as biomarkers for prognosis and therapeutic response monitoring. A particular type of EV is represented by microvesicles (MVs), which are phosphatidylserine (PS)-positive EVs (100–1000 nm) with variable shapes generated by blebbing of the plasma membrane of activated cells [ 11 , 33 ]. MVs transport miRNAs, exhibit markers from their cells of origin, such as EGFR, its mutant variant (EGFRvIII) or epithelial cell adhesion molecule (EpCAM) [ 12 , 34 ], and have been shown to have diagnostic and therapeutic potential in various pathologies, including GB [ 24 , 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%